Ways of Improvement of the Wheat Value Chain in the Republic of Armenia - Voskanyan, Ashot; Mnatsakanyan, Karine; Ghazaryan, Margo (Bulletin of Yerevan University G: Economics, 2024)
The current system of food security in the Republic of Armenia is ineffective due to organizational, management, economic, financial and other factors. Essentially, the infrastructures and links included in the purchase, processing and value chains of agricultural products do not function systematically. Valuing the role of farms in the value chain of agricultural products and adjusting and stabilizing the expected income level remains on the agenda. The purpose of the study of the article is to highlight the place and role of the agricultural holdings by analyzing the value chain of wheat in Armenia, to justify the implementation of complex approaches of branch policy measures. The objectives of the study of the article are to analyze the value chain of wheat production, the activities of the main actors, the existing problems and solution paths in the production link of the value chain. Dialectical, scientific abstraction, analysis methods were used during the research. The informational and methodological basis for the article was the conducted telephone surveys, newsletters and publications of the Statistical Committee of the Republic of Armenia, materials of magazines and various scientific articles. Grain production in Armenia should be considered among the sectoral priorities of development, the policy aimed at increasing the level of wheat production and self-sufficiency should be systemic and targeted. As a result of the research, the need for group classification of agricultural farms engaged in wheat production is presented, combining production and economic indicators and the application of cluster approaches aimed at the effective functioning of the wheat value chain.